Effectiveness of Rituximab in Maintaining Remission Status at One Year in Children with Nephrotic Syndrome in A Tertiary Care Hospital - Pillai, Asha; Uthup, Susan (Indian Journal of Pharmacy Practice)
Introduction: Nephrotic syndrome is a prevalent disorder in children, marked by the abnormal excretion of protein from the bloodstream into the urine due to compromised glomeruli. Conventional treatments such as corticosteroids and immunosuppressive medications, often lead to relapses and may have adverse effects. This study investigated the efficacy of Rituximab in sustaining remission for one year in paediatric patients with nephrotic syndrome at a tertiary care facility. Objectives: The study's objective was to assess the effectiveness of Rituximab on remission status in children with steroid-sensitive nephrotic syndrome in a hospital that provides a tertiary care facility as assessed by the number of hospital admissions. Materials and Methods: It was a prospective observational study design and children registered in the Paediatric Nephrology unit of SAT hospital since October 2023 were consecutively recruited. In this study, 41 children (2-16 years) diagnosed with steroid-sensitive nephrotic syndrome who are on Rituximab only were observed. Written informed consent was obtained from parents or legal guardians and assent from children over 10. Those with secondary nephrotic syndrome or steroid-resistant nephrotic syndrome were excluded from the study. Two doses of intravenous Rituximab were administered weekly according to the standard infusion protocol. Results: Results revealed that 84% of participants achieved complete remission at one-year post-Rituximab treatment. Conclusion: The study concluded that Rituximab is a highly effective treatment option that is being utilised more frequently to initiate or extend clinical remission in paediatric patients with nephrotic syndrome. Reducing hospital admissions suggests that Rituximab contributes to more stable disease control and better long-term outcomes in this patient population.
Keywords: Paediatric Nephrotic syndrome; Remission; Rituximab infusion; Steroid-dependent; Nephrotic syndrome; Steroid side effects